Chemical and ecological state of the waters in the Novik Bay (Russky Island, Peter the Great Bay, Japan Sea) - Nadezhda K. Khristoforova; Yulia E. Degteva; Ksenia S. Berdasova; Alexander A. Emelyanov; Alexander Yu. Lazaryuk (Известия ТИНРО)
Chemical and ecological state of the Novik Bay waters is described on the data of surveys conducted in summer, autumn, winter, and spring of 2014-2015. Lowered content of dissolved oxygen is noted for summer, with occasional decreasing to 5-6 mg/L that is below the standard summer value for fishery ponds. However, the oxygen content restores quickly in autumn, up to 12 mg/L, that is conditioned by hydrodynamic activity, water temperature decreasing, and phytoplankton blooming. The latter process is confirmed by high values of BOD5 (4.44-5.58 mgO2/L) in autumn. Winter conditions under the sea ice are satisfactory for marine organisms: dissolved oxygen content is > 4 mg/L in the whole water column that is close to the standard winter value for fishery ponds.